2019
DOI: 10.1093/gerona/glz168
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and C-Reactive Protein Levels Are Associated With Frailty in Older Spaniards: The Toledo Study for Healthy Aging

Abstract: High-sensitivity C-reactive protein (hsCRP) and homocysteine (Hcy) are inflammation markers but are also related to cardiovascular diseases, disability, or higher risk of death. Although inflammation is considered to be associated with frailty, data regarding the association between hsCRP or Hcy and frailty are controversial or scarce, especially with respect to their association with prefrailty. Thus, our objective was to study the association of hsCRP and Hcy with prefrailty and frailty in 1,211 Spanish men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…According to the previous reports, hyperhomocysteinemia (HHcy, elevated Hcy) disrupts blood-retinal barriers (BRBs) (Mohamed et al, 2017) and the retinal pigmented epithelium (RPE) (Ibrahim et al, 2016) and also induces epigenetic modifications (Elmasry et al, 2018). Also, studies have identified a strong association between HHcy and inflammation in both human and experimental models (Liu et al, 2012;Álvarez-Sanchez et al, 2019;Fang et al, 2019). However, the relationship between Hcy and RMC is rarely addressed.…”
Section: Homocysteinementioning
confidence: 99%
“…According to the previous reports, hyperhomocysteinemia (HHcy, elevated Hcy) disrupts blood-retinal barriers (BRBs) (Mohamed et al, 2017) and the retinal pigmented epithelium (RPE) (Ibrahim et al, 2016) and also induces epigenetic modifications (Elmasry et al, 2018). Also, studies have identified a strong association between HHcy and inflammation in both human and experimental models (Liu et al, 2012;Álvarez-Sanchez et al, 2019;Fang et al, 2019). However, the relationship between Hcy and RMC is rarely addressed.…”
Section: Homocysteinementioning
confidence: 99%
“…MetS is reported to be highly correlated with type 2 diabetes, cerebrovascular diseases, cardiovascular diseases, and cancer (colorectal, pancreatic, and breast cancer), which are the main causes of mortality among elderly people in South Korea [ 15 , 16 , 17 ]. These typical risk factors are associated with high levels of C-reactive protein and homocysteine, which indicate a pro-inflammatory state in the blood vessels [ 18 ]. The pro-inflammatory state causes hyper-viscosity by activating blood coagulation reactions, increasing the level of plasminogen activator inhibitor (PAI)-1 or fibrinogen [ 19 ], and increasing the level of low-density lipoprotein cholesterol (LDL-C).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of metabolic biomarkers provides excellent predictive value for distinguishing between each disease type and healthy people and those with disease. Common risk factors for CVD include serum lipids (specifically including total cholesterol, triglycerides, and apolipoproteins), as well as C-reactive protein (CRP) and Hcy (19). Hcy is a degradation product of the process of protein metabolism.…”
Section: Discussionmentioning
confidence: 99%